A nociceptive-nociplastic spectrum of myofascial orofacial pain: insights from neuronal ion channel studies - Chuinsiri, Nontawat; Tiskratok, Watcharaphol; Jorns, Teekayu Plangkoon (Frontiers in Cellular Neuroscience, 2024)
Myofascial orofacial pain, traditionally viewed as a nociceptive pain condition, also exhibits characteristics consistent with nociplastic pain-pain arising from altered nociception without clear evidence of tissue damage. Evidence supporting myofascial orofacial pain as nociplastic pain includes clinical observations of central sensitisation in patients, even in the absence of visible inflammation. Sensitisation is characterised by heightened responsiveness of nociceptive neurons to normal stimuli or activation by normally subthreshold stimuli, either in the peripheral or central nervous system. It is linked to maladaptive neuroplastic changes, including increased functional potentiation and altered expression of neuronal ion channels, receptors and neurotransmitters. This mini-review presents insights from existing evidence regarding altered nociception and its relation to changes in the expression of neuronal ion channels in myofascial orofacial pain. Increased expression of transient receptor potential (TRP) vanilloid 1 channels (TRPV1), TRPV4, TRP ankyrin 1 channels (TRPA1), Piezo2 channels, P2X3 purinergic receptors, N-Methyl-D-Aspartate (NMDA) receptors and voltage-gated calcium channels in the trigeminal ganglion of rodents has been observed in association with myofascial orofacial pain. This evidence highlights the role of neuronal ion channels in the pathophysiology of myofascial orofacial pain and supports the involvement of nociplastic mechanisms.